THE EFFECT OF ORAL STIMULATION ON THE SUCTION REFLEXES OF LOW BIRTH WEIGHT INFANTS - Fatmawati, Lilis; Syaiful, Yuanita; Tsai, Mei-Ling (SYNTHESIS Global Health Journal, 2025)
Background. Low Birth Weight Infants (LBWIs) often experience oral feeding difficulties due to organ immaturity, which can hinder their overall care and increase mortality risk. One intervention to address weak suction reflexes is early oral stimulation, involving gentle massage around the mouth to activate muscle tissue. This study aimed to examine the effect of oral stimulation on the suction reflexes of LBWIs. Research Method. A pre-experimental one-group pretest-posttest design was used. The study involved 28 LBWIs selected through purposive sampling from a population of 30 infants. The independent variable was oral stimulation, and the dependent variable was the infants’ suction reflexes. Oral stimulation was administered once daily for 15 minutes over seven consecutive days. Data were collected using a standard oral stimulation procedure and observation sheets to assess suction reflexes. Findings. Before the intervention, 15 infants (54%) showed poor suction reflexes. After the seven-day stimulation, 18 infants (64%) demonstrated improved suction reflexes. Statistical analysis using the Wilcoxon Signed Rank Test showed a significant effect (p = 0.000), indicating that oral stimulation positively influenced the development of suction reflexes in LBWIs. Conclusion. oral stimulation is effective in enhancing suction reflexes among LBWIs. Nurses are encouraged to implement this simple, non-invasive intervention to promote faster recovery, shorten treatment duration, and reduce healthcare costs.